(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Employee performance is a major concern for businesses in today’s competitive world. The impact of monetary benefits on employee performance is one of the important factors that affect organizational performance. The purpose of this study is to examine the influence of monetary benefits on employee performance in 3S Center, Valenzuela City. Monetary benefits are tangible rewards, such as salaries, bonuses, and incentives that employees receive from the organization. The study will look at how these monetary benefits positively or negatively influence employee performance, productivity, and motivation in the workplace. By understanding this relationship, organizations may be able to improve their employee performance and overall organizational success. The impact of monetary incentives on employee performance at 3S Center, Valenzuela City, or any work has been widely explored in the discipline of Human Resource Management (HRM). Employers frequently utilize monetary rewards such as salaries, bonuses, and other incentives to encourage and keep their staff. The researchers concluded that monetary advantages had a beneficial influence on employee performance. Employees who are fairly compensated and suitably recognized for their achievements are more engaged and productive at work. On the other hand, employees who are underpaid or feel underappreciated are more likely to be disengaged and may eventually quit their positions. However, it is important to note that monetary benefits are not the only factor that influences employee performance. Other elements that influence employee motivation and performance include job happiness, work environment, and opportunity for growth and development. In conclusion, while monetary incentives are crucial in motivating and keeping people, they should be viewed as one piece of a broader jigsaw that incorporates other aspects that influence employee performance. It has been up for discussion for a while now whether financial incentives have an effect on workers' productivity. Some claim that monetary incentives are insufficient to increase employee performance, while others believe that monetary incentives are effective motivators. In the setting of 3S Center, Valenzuela City, monetary advantages may have a substantial impact on employee performance. The automotive sector is highly competitive, and success depends on maintaining competent and motivated personnel. Offering monetary perks like bonuses and incentives may encourage employees to work harder and perform better. Despite this, it’s critical to remember that financial rewards should be combined with a friendly and productive workplace. Simply throwing money at employees without addressing underlying issues like stress, burnout, or a lack of communication may backfire and result backfiring and resulting in lower morale and productivity. Finally, a balance of monetary and non-monetary incentives, such as professional development opportunities and recognition, may produce the best results in promoting employee performance and retention in 3S Center, Valenzuela City.